INTRACYSTIC HEMORRHAGE IN THE LUMBAR SPINE AS A CAUSE OF SUDDEN LEG WEAKNESS – A CASE REPORT - Mitrović, Vekoslav; Baščarević, Vladimir; Stolić, Radojica; Mitrović, Vladimir; Filipović-Danić, Snežana (Sanamed, 2024)
Introduction: Synovial cysts of the facet joint are rare benign changes occurring in the spinal synovial joints, predominantly in the lumbar region. Although these cysts are generally benign, intracystic hemorrhages are extremely rare and can lead to severe complications.Case Presentation: This case report details a patient who developed cauda equina syndrome due to hemorrhage within a synovial cyst in the lumbar spine.The patient's symptoms included acute radicular pain and neurological deterioration. Diagnostic imaging revealed a large synovial cyst with evidence of intracystic bleeding.Conclusion: Acute radicular pain and rapid neurological deterioration can result from a synovial cyst in the lumbar spine, particularly when complicated by intracystic bleeding. Urgent decompressive surgery and removal of the cyst resulted in complete recovery for the patient.
Keywords: synovial cysts; bleeding; leg weakness